Pengaruh Pengendalian Internal dan Audit Internal Terhadap Pencegahan Kecurangan pada Bank BCA KCP Dinoyo Kota Malang - Irma Nur Laili; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to explain the effect of internal audit internal control on fraud prevention at Bank BCA KCP Malang, Dinoyo, Malang City. The independent variable indicators of this study are Internal Control, Internal Audit. The indicator of the dependent variable of this research is Fraud Prevention. The data used is primary data, obtained from primary data by distributing questionnaires to the Head/Director/Staff of Accounting/Administration/Employee of Bank BCA KCP Dinoyo and Kawi Malang City. Sampling was carried out using purposive sampling method. The sample of this research is a total of 44 auditors and all employees of Bank BCA KCP Dinoyo Malang. Data analysis used the classical assumption test and multiple linear regression. The results of this study indicate that simultaneously the variables Internal Control and Internal Audit have a significant effect on Fraud Prevention at Bank BCA KCP Dinoyo. The results showed that partially the Internal Control variable had a positive and significant effect on Fraud Prevention. The results showed that partially the Internal Audit variable had a positive and significant effect on Fraud Prevention.Keywords: Internal control, internal audit, fraud prevention